2020
DOI: 10.1080/02615479.2020.1825662
|View full text |Cite
|
Sign up to set email alerts
|

Partnership working in the face of a pandemic crisis impacting on social work placement provision in England

Abstract: The first quarter of 2020 saw unprecedented global, national, and local changes as the world adapted to a pandemic that swept the world at an alarming rate and prompted a policy of social exclusion and social distancing. Inevitably, the pandemic impacted upon social work education and placement provision significantly. The ability to respond to the impact of the pandemic crisis within social work placements will be presented as an unprecedented wicked problem. The ability to respond to this crisis can be argue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Fenomena Covid-19 telah merubah dinamika psikologis masyarakat (Aragonés & Sevillano, 2020;Chao dkk., 2020;Zhou & Yao, 2020), dimensi sosial masyarakat (Beesley & Devonald, 2020;Nyashanu dkk., 2020), bahkan pelaksanaan pendidikan (Ellis dkk., 2020;Masri & Sabzalieva, 2020;Xue dkk., 2020). Perubahan demikian juga terjadi di Indonesia.…”
Section: Pendahuluanunclassified
“…Fenomena Covid-19 telah merubah dinamika psikologis masyarakat (Aragonés & Sevillano, 2020;Chao dkk., 2020;Zhou & Yao, 2020), dimensi sosial masyarakat (Beesley & Devonald, 2020;Nyashanu dkk., 2020), bahkan pelaksanaan pendidikan (Ellis dkk., 2020;Masri & Sabzalieva, 2020;Xue dkk., 2020). Perubahan demikian juga terjadi di Indonesia.…”
Section: Pendahuluanunclassified
“…This warrants further critical discussion about the benefice of moving to an e-placement, and solid contingency planning to provide the resourcing required for any future placements that are disrupted. Whilst self-motivation and being pro-active in learning is a general expectation in field education ( Maidment, 2010 ), to be self-directed learners, all stakeholders need to be ‘robust’ and students need to have guidance, support and resources available to them ( Beesley and Devonald, 2020 , p. 1146). This clearly has significant workload implications for academic staff and needs to be factored in.…”
Section: Discussionmentioning
confidence: 99%
“…A study of field education programmes across seven countries showed that practice placements ended or were paused ( McFadden et al , 2020 ), but the interesting difference was the ability to act quickly if the universities were in national or regional partnerships with other universities and governing bodies. In Northern Ireland and England, an assessed year in employment enabled final year students to withdraw early from their placements, and recruiting them into the social work workforce to carry forward unmet learning needs into their first year ( Beesley and Devonald, 2020 ; McFadden et al , 2020 ). Temporary amendments to social work education accreditation standards also occurred in the USA and Canada (Canadian Association For Social Work Education (CASWE), 2020 ; Council on Social Work Education (CSWE), 2020 ) with adjustments made to allow for a continuation of placement when the standard placement activities were interrupted and potentially threatened student progression and completion ( Mclaughlin et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regular supervision and safe learning environments are central to the development of students' social work identity and professional confidence (Roulston et al, 2016). Therefore, the unprecedented reduction or inability for students to participate in this agency-based learning environment challenged social work programmes globally to balance the competing needs of students to experience the roles and tasks of social work practice without eroding professional and university standards (Beesley and Devonald, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The English social work regulatory body provided a directive that social work education providers could make individual decisions about whether placements could be continued, shortened, suspended or replaced (Council of Social Work Education [CSWE], 2020). Thus, some placements were shortened if the student was meeting the expectations of the Professional Standards (Beesley and Devonald, 2020). In Northern Ireland, final year social work students were withdrawn from placement early.…”
Section: Introductionmentioning
confidence: 99%